Few-step synthesis, thermal purification and structural characterization of porous boron nitride nanoplatelets - Kostoglou, Nikolaos; Lukovic, Jelena B.; Babic, Biljana M.; Matovic, Branko Ž; Photiou, Demetris; Constantinides, Georgios; Polychronopoulou, Kyriaki; Ryzhkov, Vladislav; Grossmann, Birgit; Mitterer, Christian; Rebholz, Claus (My University, 2016)
Hexagonal boron nitride (h-BN) nanoplatelets with ~ 99 wt.% purity, 900 to 2000 nm particle width, 30 to 90 nm particle thickness, ~ 213 m2/g specific surface area (SSA), ~ 66% micropore SSA and ~ 0.85 nm average pore size were synthesized in a powder form using H3BO3 and CO(NH2)2 as precursors followed by consecutive thermal treatments under inert and oxidized atmospheres. Thermal gravimetric analysis (TGA) combined with differential scanning calorimetry (DSC), under synthetic air-flow and up to ~ 1300 °C, were employed to evaluate both purity and oxidation resistance of the product directly upon its synthesis. The h-BN powder was collected at the stage of its highest purity which, based on TGA-DSC data, corresponded to an additional heat treatment up to ~ 700 °C. The active oxidation seems to occur in the temperature range between ~ 860 and ~ 1000 °C, followed by formation of B2O3 in the final residue. Subsequently, the purified h-BN powder was extensively characterized for its structure, morphology and porosity using X-ray diffraction, scanning electron microscopy and nitrogen gas adsorption/desorption measurements at 77 K, respectively. As briefly discussed, purity and SSA seem to have a crucial role in the thermal stability and oxidation resistance of BN materials in general.
Keywords: Boron nitride; Characterization studies; Hexagonal structure; Nanoplatelets; Porous powders; Thermal purification